Video art : a guided tour - Elwes, Catherine, 1952-; University of the Arts London (London ; New York : I.B. Tauris ; London : in association with University of the Arts ; New York : In the United States of America and in Canada distributed by Palgrave Macmillan, 2005)
Video art dominates the international art world to such an extent that its heady days on the radical fringes are sometimes overlooked - often unknown. This text is a guide to video art and its history, tracing the story from the weighty Portapak equipment of the '60s and '70s to today's digital technology.
Foreword / Shirin Neshat -- Introduction : from the margins to the mainstream -- The modernist inheritance : tampering with the technology, and other interferences -- Disrupting the content : feminism -- Masculinities : class, gay and racial equality -- Language : its deconstruction and the UK scene -- Television spoofs and scratch : parody and other forms of sincere flattery -- Video art on television -- Video sculpture -- The 1990s and the new millennium.
Includes bibliographical references (pages 205-207) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Video art; Art, Modern -- 20th century; Art, Modern; Art vidéo.; Art -- 20e siècle.; video art; ART -- Mixed-Media.; Art, Modern; Video art; Videokunst; 1900-1999